The OFIS model: an efficient tool for assessing ozone exposure and evaluating air pollution abatement strategies. (1st January 2000) - Moussiopoulos, N.; Sahm, P.
The Ozone Fine Structure (OFIS) model describes transport and chemical transformation processes in an urban plume at very low computational effort. This newly developed Eulerian model may be used for calculating ozone levels for individual situations as well as for deriving ozone exceedance statistics based on large-scale meteorological and long-range transport information over a longer time period. Results are presented from the application of the OFIS model to Stuttgart for the period April to September 1990. Compared to measurements, OFIS satisfactorily describes both the absolute maximum ozone values and cumulative AOT60 values in the area of interest. Results of the OFIS model allow conclusions regarding the influence of assumed ozone emission reductions on the urban scale to be drawn.